Influence of intrapulmonary percussive ventilation in upright position on gastro‐oesophageal reflux in infants. Issue 10 (24th February 2016) - Van Ginderdeuren, F.; Kerckhofs, E.; Deneyer, M.; Vanlaethem, S.; Buyl, R.; Vandenplas, Y.
Summary: Objectives: To determine the influence of physiotherapy using intrapulmonary percussive ventilation on gastro‐oesophageal reflux (GOR) in infants <1 year. Methods: In this controlled trial with intra‐subject design, children were studied using multichannel intraluminal impedance pH (pH‐MII) monitoring over 24 hr, during which they received one 20‐min session of intrapulmonary percussive ventilation in upright position (IPVR ), 2 hr after their latest feeding. Two hours after each feeding, the number of reflux episodes (RE) over a 20‐min period was registered for each infant and a mean per 20 min was calculated in order to obtain a baseline value. The number of RE during IPVR intervention was compared to baseline. Results: Fifty infants with a median age of 133 days were recruited of whom 21 were diagnosed with pathological GOR. During IPVR, the incidence of RE in the entire group was significantly lower compared to baseline; median (inter‐quartile range [IQR]) 0 (0–1) versus 0.71 (0–1.33) RE, respectively, P  = 0.003. The subgroup with abnormal GOR showed also a significant decrease of RE during IPVR ; median (IQR) 0 (0–1) versus 1.17 (0.55–2.16) RE, respectively, P  = 0.03. No difference was detected in the group with normal reflux; median (IQR) 0.6 (0–1) compared to 0 (0–1) RE, respectively, P   =  0.34. Conclusion: IPVR does not induce, nor aggravate GOR in infants without and with pathological GOR, respectively, but on the contrary decreases the number of RE in patients with pathological reflux.Pediatr Pulmonol. 2016;51:1065–1071. © 2016 Wiley Periodicals, Inc.